Autoimmune Hepatitis with Acute Presentation: Clinical, Biochemical, and Histological Features of 126 Patients - Álvaro Urzúa; Carolina Pizarro; Abraham Gajardo; Rafael Poniachik; Claudia Pavez; Máximo Cattaneo; Javier Brahm; Laura Carreño; Jaime Poniachik (Canadian Journal of Gastroenterology and Hepatology)
Introduction. Autoimmune hepatitis (AIH) is a chronic liver disease with a relevant inflammatory component and an unknown etiology. Evidence for clinical characteristics and risk factors in large cohorts of patients with acute AIH (AAIH) is lacking. We clinically characterized patients with AAIH, the prevalence of a combined adverse outcome (death or liver transplantation (LT)), and its risk factors. Methods. A retrospective study of adult patients diagnosed with AAIH at three centers (Santiago, Chile; 2000–2018) was conducted. Clinical and laboratory characteristics were obtained. A liver biopsy was performed for all patients. Descriptive statistics and logistic regression models were used. Results. A total of 126 patients were admitted; 77% were female, 33 (26.2%) had a severe presentation, and 14 (11.1%) had a fulminant presentation. Overall, 24 patients (19.0%) lacked typical autoantibodies, and 26.2% had immunoglobulin G levels in the normal range. The most frequent histological findings were plasma cells (86.5%), interface hepatitis (81.7%), and chronic hepatitis (81.0%). Rosettes were uncommon (35.6%). Advanced fibrosis was present in 27% of patients. Combined adverse outcomes occurred in 7.9% of cases, all fulminant with histological cholestasis. Alkaline phosphatase, bilirubin, and prothrombin less than 50% were independent risk factors for in-hospital death or LT (p value <0.05). Although corticosteroid treatment was associated with better outcomes (OR 0.095, p value = 0.013), more severe patients were less likely to receive this therapy. Discussion. In this large cohort of patients with AAIH, clinical characteristics differ from those reported in patients with chronic AIH. Fulminant hepatitis, histological cholestasis, alkaline phosphatase, bilirubin, and prothrombin were associated with death/LT.